Implementasi metode eliminasi Gauss-Jordan dan dekomposisi Crout dalam memprediksi volume lalu lintas - Munawaroh, Eva Lailatul; Isnarto, Isnarto (Universitas Negeri Semarang, 2021)
Traffic volume is the number of vehicles passing at a point on a particular road at a certain period of time. The main purpose of this study was to predict the volume of traffic on Pemuda Street Semarang City using Gauss-Jordan elimination and Crout decomposition methods and determine alternative solutions to overcome congestion. Data collection is done by traffic counting at every intersection along Pemuda Street, Imam Bonjol Sreet, and Kapten Pierre Tendean, Semarang City. The linear equation system model is formed based on the data that has been obtained and then processed using both methods to find the number of vehicles passing through. This study concluded that the volume of traffic obtained using the Gauss-Jordan elimination and Crout decomposition at each track point along Pemuda Street overall from morning to noon and evening experiencing density. From both methods show that the Gauss-Jordan elimination method is more effective and efficient. The comparison of the two methods can be seen from the many steps of completion, the number of arithmetic operations, speed, and accuracy of obtaining a solution.